Optimization of the drying parameters for the short-form spray dryer producing powdered egg with 20% tapioca starch additive. (7th September 2015) - Masilungan-Manuel, Joanna Tess; Manuel, Mark Christian E; Lin, Po Ting; Soriano, Allan N
Spray drying is one of the common methods of preserving eggs. A study had shown that addition of 20% tapioca starch to liquid egg prior to drying increases the shelf-life of the powdered product. However, although the said factor has been identified, production in a larger capacity is still a problem. One way to solve this predicament is to identify the optimum drying parameter that would produce a higher yield of dried eggs but retain the quality of the desired product such as the moisture content and water activity. The key issue in optimizing the dryer operation is flow stability wherein the airflow patterns, such as velocity, temperature, and relative humidity, existing inside the drying chamber are considered as the primary factor that influences the histories of the droplets produced. In this article, the author used ANSYS-Fluent version 14.5, a computational fluid dynamics software, to analyze the flow pattern of the continuous phase and to track the particle histories of the disperse phase inside the short-form drying chamber that produces powdered egg with 20% tapioca starch additive. Simulations for the short-form dryer showed that the optimized inlet air temperature and outlet particle temperature were 438 and 385 K, respectively. Based on the results, the calculated moisture content and water activity are 4.55% and 0.02a w, respectively. Note that the critical moisture content and water activity for powdered eggs are 5% and 0.4a w, respectively. The values beyond these limits will cause abrupt spoilage of the dried egg.